Analisis Pengaruh Cita Rasa, Label Halal, dan Diversifikasi Produk terhadap Keputusan Beli Konsumen Pada Produk Olahan Tuna Inggil Pacitan Jawa Timur (Studi Kasus Pada UD Bina Makmur Pacitan, Jawa Timur) - Sugeng Nugroho (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2016)
The results of this research indicate that taste variable (X1), halal label (X2), and product diversification (X3) simultaneously have a positive relationship on consumer purchasing decision (Y). Based on the results of data analysis, R square value is 0.417. Simultaneously, hypothesis test resulted in sig. value of 0.000 is smaller than alpha 0.05. So it can be concluded that X1 and X3 have a significant effect simultaneously toY. The results of this research also show variable X1, X2, and X3 have a partial positive relationship to Y. Result of hypothesis test of taste variable shows that sig. 0.000, Halal label variable has a sig. 0.053, and product diversification variable has a sig. 0,048. Therefore, it can be concluded that taste and product diversification has a significant influence on consumer purchasing decision on processed product of tuna Inggil Pacitan East Java, where as halal label variable has ainsignificant effect or indirectly becomes intevening variable in this research. The result of regression equation is Y = 4,888 + 0,252 X1 + 0,155 X3.